A CARE-compliant article: a case report of pleural empyema secondary to Klebsiella pneumoniae liver abscess with a hepatopleural fistula. Issue 16 (April 2020) - Lee, Eun Ji; Lee, Kyung Hee; Kim, Jun Ho; Jeon, Yong Sun; Kim, Jung Soo
Abstract: Introduction: Klebsiella pneumoniae liver abscess (KPLA) is often associated with accompanying metastatic complications such as septic pulmonary embolism, brain abscess, and endophthalmitis. Pleural empyema secondary to a KPLA is a very unusual finding, made even more rare with the presence of a hepatopleural fistula. Patient concerns: An 81-year-old woman presented with aggravated dyspnea. Diagnosis: The patient was diagnosed with KPLA with empyema through computed tomography (CT) scan findings and pleural fluid culture. Interventions: The empyema was drained by thoracostomy, and treatment with empirical antibiotics was initiated. After early removal of the chest tube, the liver abscess as well as the empyema increased. An additional liver abscess drainage procedure was performed. Outcomes: The fever resolved and dyspnea improved following drainage of effusion. Three days later, the follow-up chest radiograph showed decreased pleural effusion. Conclusion: Pleural empyema is a rare but fatal complication secondary to KPLA. Additionally, the discovery of a hepatopleural fistula on a CT scan (multiplanar reconstruction image) made this case even more rare. Both, the liver abscess and pleural empyema, were effectively drained through the fistula tract with drainage procedure, thoracostomy, and additional liver abscess drainage. Prompt diagnostic evaluation, using an imaging modality such as CT, and early drainage management with intravenous antibiotics can improve clinical outcome.